Double Layer Conducting Salts: (CNB-EDT-TTF)4X, X = ClO4−, ReO4−, and SbF6−; Electrical Transport and Infrared Properties - Sandrina Oliveira; Ana Cristina Gonçalves; Gonçalo Oliveira; Dominik Günther; Andrea Rohwer; Vasco Gama; Elsa Branco Lopes; Isabel Cordeiro Santos; Sandra Rabaça; Manuel Almeida; Martin Dressel (Crystals, 2019)
Two new members of the family of bilayer compounds (CNB-EDT-TTF)4X, (CNB-EDT-TTF = 5-cyanobenzene-ethylenedithio-tetrathiafulvalene) with anions X = ReO4− and SbF6− are reported, their electron transport and optical properties investigated, and then compared to the ClO4− salt that was previously described. These compounds share the same structural type, i.e. bilayers of donors, which are packed in a β”-type pattern and then separated by layers of highly disordered anions. The absolute values of the electrical resistivity measured in single crystals within the layers were found in the range of 5 to 18 (cm)−1, with a significantly sample dependence being ascribed to intrinsic disorder effects. The ClO4− and SbF6− salts exhibit metallic behavior with the resistivity decreasing upon cooling almost linearly with temperature until a broad minimum is reached between 15 and 80 K, depending on crystal quality; this is followed by an upturn of resistivity reaching values at T = 1.5 K that were comparable to those attained at room temperature. The electrical resistivity of the ReO4− salt follows a thermally activated behavior already at T = 300 K, although with a small activation energy in the range 16−18 meV. Thermoelectric power measurements yield large positive values (75−80 µV/K) at ambient temperature with a metallic behavior that is identical for all compounds. Temperature and polarization dependent infrared reflection measurements on single crystals of (CNB-EDT-TTF)4X salts, with X = ClO4−, ReO4−, and SbF6−, have been performed to obtain the optical conductivity and analyze the electronic and vibrational properties. For (CNB-EDT-TTF)4ClO4 the molecular vibrations exhibit a significant variation below T = 23 K, which suggests a charge localization phenomena.